Diode laser in the excision of intraoral fibroma: A safe tool for minimally invasive dentistry - Madhuri Alankar Sawai,; Pooja Sharma,; Zeba Jafri,; Nishat Sultan, (Indian Journal of Case Reports, 2021)
Intraoral fibroma is a common lesion that develops in the oral cavity following trauma or tissue injury. It has a strong female predilection and is more frequently seen in the third and fourth decades of life. The most common site of traumatic fibroma is buccal mucosa along the plane of occlusion. The conventional method for excision of fibromas is using surgical blades. However, this method has certain disadvantages such as excessive bleeding and pain to the patient during the excision. Postoperatively, there can be delayed wound healing with occasional scarring. With the introduction of diode lasers for soft-tissue excisions in dentistry, we can now overcome these limitations. Here, we present the case series of two cases of intraoral fibroma. In this case series, intraoral fibroma was excised using a diode laser. It was observed that in both cases, the healing was much faster. There was minimal intraoperative bleeding. Furthermore, the surgical time reduced substantially and the patient was more comfortable during the procedure as well as in the postoperative phase. Thus, the diode laser has been found to be safe, less painful, and with better post-operative outcomes.